Impact of Grazing Methods on Forage and Cattle Production - Joao Vendramini; Lynn Sollenberger (EDIS)
SS-AGR-133, a 5-page fact sheet by Joao Vendramini and Lynn Sollenberger, describes the advantages and disadvantages of rotational grazing vs. continuous grazing. Includes figures and references. Published by the UF Department of Agronomy, January 2007.